2009
DOI: 10.1111/j.1471-0307.2008.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid levels and physicochemical properties of herby brined cheese, a traditional Turkish cheese

Abstract: In this study, some gross chemical compositions and fatty characteristics of herby cheeses were investigated. In the present study, the cheeses used as materials were collected from 10 different plants. The cheeses were made from sheep milk, cow's milk or a mixture of them, and stored in brine at 7-8°C and analysed for some proximate chemical compositions and fatty acid composition after 150 days of ripening. Capric acid, palmitic acid, oleic acid, short-chain fatty acids, medium-chain fatty acids, longchain f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
(59 reference statements)
2
8
0
Order By: Relevance
“…Lipolysis results in the formation of free fatty acids (FFAs), and statistically significant (P < 0.05) changes were recorded between control and cheese samples belonging EG I, where herb extract added in cheese body. Two groups of authors reported very similar results for 20 traditional Turkish ripened herby cheese [13,34]. By comparing the results of our testing with the results that are obtained in specific characteristics of Pirotski Kachkaval study [35,36] minor differences were observed in mean values of chemical parameters (lower total solids and fat content and higher content of fat in total solids), and protein content is very similar.…”
Section: Physicochemical Analyses Of Pirotski Kachkavalsupporting
confidence: 76%
“…Lipolysis results in the formation of free fatty acids (FFAs), and statistically significant (P < 0.05) changes were recorded between control and cheese samples belonging EG I, where herb extract added in cheese body. Two groups of authors reported very similar results for 20 traditional Turkish ripened herby cheese [13,34]. By comparing the results of our testing with the results that are obtained in specific characteristics of Pirotski Kachkaval study [35,36] minor differences were observed in mean values of chemical parameters (lower total solids and fat content and higher content of fat in total solids), and protein content is very similar.…”
Section: Physicochemical Analyses Of Pirotski Kachkavalsupporting
confidence: 76%
“…These findings were similar to that reported by Kaya () in Gaziantep cheese, Temiz et al . () in herby cheese and Westermann et al . () in cream cheese.…”
Section: Resultsmentioning
confidence: 87%
“…Different salt concentrations and brining time are the most important factors affecting the salt content of cheese. [32] Maximum protein content was found to be 24.63% (CHS1) while the minimum was 18.64% (CHS9). The highest protein content of CHS1 could be attributed to higher dry matter content.…”
Section: Composition Of Mihalic Cheesementioning
confidence: 96%